1997
DOI: 10.1002/(sici)1099-0496(199712)24:6<391::aid-ppul3>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of tidal flow volume loop indices in neonates and children with and without asthma

Abstract: The tidal flow volume (TFV) loop ratios of (1) time to peak flow (tPTEF) to total expiratory time (tE) [tPTEF/tE] and (2) volume to peak flow (VPTEF) to expired volume (VE) [VPTEF/VE] are reported to decrease with age in early life, and to decrease in subjects with obstructive airways disease (OAD). However, the mechanisms behind these changes are not well known. Thus, we reanalyzed data from 24 healthy neonates (mean birthweight: 3.49 kg ± 0.42 kg (SD)), 26 presently asymptomatic asthmatic children (age: 33 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…Both values for preterm and term infants reported by Latzin et al22 were lower than in our study, but their infants were chronologically much older. Our results were comparable to those from other studies 19–21…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both values for preterm and term infants reported by Latzin et al22 were lower than in our study, but their infants were chronologically much older. Our results were comparable to those from other studies 19–21…”
Section: Discussionsupporting
confidence: 92%
“…It has previously been shown that the flow parameter t PTEF /t E is dependent on the postnatal age. The t PTEF /t E decreases during the first week of life from 45% at birth to 32% at 5 days19, 20 and then further during first 2 months of life 21. In the current study, the preterm infants were significantly older chronologically than the term infants at the time of the study (Table 1).…”
Section: Discussionmentioning
confidence: 46%
“…The reference values for VPTEF/VE, TEF75, TEF50, and TEF25 in healthy neonates are very limited. The decrease observed in VPTEF/VE during the neonatal period was in agreement with the results of previous studies 23,32 . Lodrup Carlsen et al 23 reported a mean VPTEF/VE value of 0.40 for male and 0.37 for female neonates at 2 days of age.…”
Section: Discussionsupporting
confidence: 91%
“…Tidal breathing measurements included flow and volume signals, and were assessed by professional staff. Lung function was graded as normal, mild, moderate, severe, or extremely severe according to three-component score system which could reflect underlying obstructive airways disease [14,15] as shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%